ANALISIS PENGARUH SOSIALISASI PAJAK DAN PENGGUNAAN E-FILING TERHADAP KEPATUHAN WAJIB PAJAK: KEPATUHAN WAJIB PAJAK - Syifa Siti Hanifah Indrawan; Siti Asmonah (Yayasan Kayyis Mulia Jaya, 2025)
According to the observed phenomenon, the annual income of the region continues to increase every year. This study aims to analyze the impact of tax socialization and the use of e-filing on taxpayer compliance, focusing on individuals in the South Tangerang City DPRD environment, providing a more specific picture of how government policies and programs can influence tax compliance among civil servants and the surrounding community. The type of research used in this study is associative research, with a quantitative approach to re-test hypotheses that have been tested by previous researchers, using primary data obtained directly through questionnaires that will be distributed to each respondent. With a sample of 50 respondents that can be processed. The research results show that tax socialization and the use of e-filing have a significant partial effect on taxpayer compliance. Simultaneously, tax socialization and the use of e-filing have a significant effect on taxpayer compliance. These findings indicate that tax socialization and the use of e-filing are among the factors contributing to increased taxpayer compliance. The Secretariat of the South Tangerang City DPRD is advised to conduct regular training for employees and taxpayers on the use of e-filing and tax understanding to improve the knowledge and skills of employees. Keywords: Tax Socialization, Use of E-filing, Taxpayer Compliance, Individual Taxpayers.